Investigation influence of store type on emotional state of consumer in the urban purchase - Andrii Halkin; Kseniia Bliumska-Danko; Olena Smihunova; Elena Dudnyk; Iryna Balandina (Foundations of Management, 2019)
The shopping service of the store plays an important role in shaping the opinions of custom-ers in a store. Endless progress has been made on quality management of consumer services confirmed through numerous methods and standards that are based on consumers. A typical consumer receives a large amount of information in the shopping process. In the process of perception of this information, consumer must not only find necessary data, but also process, analyze, and evaluate this date, and weigh the pros and cons, relate it to his own needs, and at the end, make a decision: to buy or not to buy a certain product. All these reflect on consumer's fatigue, stress, and other negative fallings ob-tained during any shopping. In this case, the buyer can make the wrong choice and the quality of his decisions would deteriorate. Therefore, investigation influence of store type on the emotional state of consumers in the urban purchase provides significant reserve for marketing development in this sphere. Research provides explanation of emotional fatigue on the type of stores. The regression mod-els describing the shift in emotional state of the buyer in purchase process of different type of shops were obtained. Research was conducted in the residential area of Kharkiv, Ukraine. The presented model shows the average value of the indicator of the emotional system of buyers after shopping, which can be used to determine the likelihood of shopping on the basis of emotional fatigue.
Keywords: M31; M39; C93; D19; L69; 650; customer; emotion; state; purchase; GSR